Daya Tetas Telur dan Sintasan Larva Dari Hasil Penambahan Madu pada Bahan Pengencer Sperma Ikan Nila (Oreochromis niloticus) - Ayer, Yunus; Mudeng, Joppy; Sinjal, Hengky (e-Journal BUDIDAYA PERAIRAN, 2015)
The objective of research was to determine the concentration of honey in sperm dilution  for improving hatching rate of egg and survival of nile tilapia larvae (Oreochromis niloticus).The number of fish used was five pairs broodstock. Dilution substance was NaCl and honey.  Observations were conducted on spermatozoa motility, fertility and egg hatching rate. Experimental design used was complete randomized design. Sperm dilution substance was prepare by disolving honey  (0 mL; 0,60 mL; 0,65 mL dan 0,70 mL) in 100 mL; 99,40 mL; 99,35 mL and  99,30 mL NaCl respectively.  Each dilution was homogenized using aerator for 15 minutes. Fertilization was done 12 hours after ovulation.  Egg hatching rate was observed after ovulation. Research results showed the use of honey had significant effet on egg hatching rate, but not on larval survival.  Treatment D (0,70 mL honey in 99,30 mL NaCl) had the highest hatching rate (77.33%). Dilution ratio 1:60 was the best indicated by spermatozoa motility 96.66%, fertility 71.65, hatching rate 70% and larval survival 81.67%   Keywords : honey, egg hatching rate, larval survival, Oroechromnis niloticus